2022
DOI: 10.3389/fpls.2022.890568
|View full text |Cite
|
Sign up to set email alerts
|

Development of Wide-Compatible Indica Lines by Pyramiding Multiple Neutral Alleles of Indica–Japonica Hybrid Sterility Loci

Abstract: Since the development of indica hybrid rice in the 1970s, great success has been achieved in hybrid rice production in China and around the world. The utilization of inter-subspecific indica–japonica hybrid rice has always been considered due to its stronger heterosis characteristics. However, indica–japonica hybrids face a serious problem of sterility, which hinders the exploitation of their heterosis. In the past decades, the genetic basis of indica–japonica hybrid sterility has been well studied. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…These suggested that the accessions carrying a few NFAs provide potential targets for the BCAA biofortified rice breeding programs via the loci pyramiding strategy. It was successfully applied in the improvement of various agronomic traits, such as plant height, grain number, hybrid sterility, and disease resistance [ 57 , 58 , 59 , 60 , 61 ]. In the present study, higher BCAA levels were mostly shown in the japonica accessions than in the indica accessions ( Figure 1 A–C), suggesting that the japonica rice has the potential of the increase in the BACC content in indica rice through the direct hybridization with elite varieties.…”
Section: Discussionmentioning
confidence: 99%
“…These suggested that the accessions carrying a few NFAs provide potential targets for the BCAA biofortified rice breeding programs via the loci pyramiding strategy. It was successfully applied in the improvement of various agronomic traits, such as plant height, grain number, hybrid sterility, and disease resistance [ 57 , 58 , 59 , 60 , 61 ]. In the present study, higher BCAA levels were mostly shown in the japonica accessions than in the indica accessions ( Figure 1 A–C), suggesting that the japonica rice has the potential of the increase in the BACC content in indica rice through the direct hybridization with elite varieties.…”
Section: Discussionmentioning
confidence: 99%
“…According to the well-known theory put forth by Ikehashi and Araki (1986), F1 sterility was mostly brought on by embryo sac abortion, which was determined by the genotype of S 5 located in chromosome 6, and indica was S 5 i S 5 i in genotype as well as japonica S 5 j S 5 j (Yang et al, 2009;Zhang et al, 2020;Seo et al, 2020;Kallugudi et al, 2022) hence The S 5 locus on chromosome 6 became the primary genetic cause of embryo sac sterility due to several allelic interactions (Lee et al, 2021;Ouyang et al, 2022). Nevertheless, hybrid fertility was decreased as a result of interactions between the indica and japonica alleles at each of the loci (Xie et al, 2019;Guo et al, 2022;Kallugudi et al, 2022). Yang further explained that because to gene interactions, the indica and japonica parent types' S5iS5j hybrids were also infertile S 5 i and S 5 j .…”
Section: Introductionmentioning
confidence: 99%
“…When crossed to indica or japonica subspecies, WCVs can overcome obstacles to reproduction and result in fertile hybrids. Hybrids between indica and japonica parent lines that carry the S 5 n (wide-compatible gene) would have high or normal fertility regardless of whether they have the S 5 nS 5 i or S 5 nS 5 j genotype Ghaleb et al, 2020;Guo et al, 2022). Wide-compatibility varieties (WCVs) allowed the reproductive barrier between the indica and japonica subspecies to be breached and gave rice breeding programs the opportunity to create inter-sub specific hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…The HJX74-SSSLs were widely used to detect QTLs for traits of agronomic importance (Zhang et al, 2012 ; Zhu et al, 2014 , 2018 ; Yang et al, 2016 , 2021a , b ; Zhou et al, 2017b ; Pan et al, 2021 ; Zhan et al, 2021 ; Fu et al, 2022 ), to clone genes of functional importance, and to mine alleles of functional variants (Zeng et al, 2006 ; Teng et al, 2012 ; Wang et al, 2012 ; Fang et al, 2019 ; Sui et al, 2019 ; Gao et al, 2021 ; Zhan et al, 2022 ). Using the HJX74-SSSL library as a platform for rice design, a series of cytoplasmic male sterility (CMS), maintainer and restorer lines, and wide-compatible indica lines (WCILs) were developed (Dai et al, 2015 , 2016 ; Luan et al, 2019 ; Guo et al, 2022 ). Recently, the SSSLs were used to detect QTLs controlling SER in rice.…”
Section: Introductionmentioning
confidence: 99%